Maine’s Connected Food System: On the Web and Online - Ives, Barbara; Merrill, Sam (Maine Policy Review, 2011)
The authors of this case study discuss how modern communications via the internet are expanding opportunities in Maine’s food system, ranging from consumers’ buying clubs to food resource maps to “Maine Ag Trader,” a website that enables producers and consumers to connect and find what they need.
Keywords: Maine; food system; e-commerce